An empirical assessment of hotel managers turnover intentions: the impact of organizational justice / Siti Zuraini Ramley Alan ... [et al.] - Ramley Alan, Siti Zuraini; Md. Radzi, Salleh; Hemdi, Mohamad Abdullah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2009)
A high turnover of managers within the hotel industry has become one of the major concerns to the researchers and practitioners. In line with this view, this paper investigates the relationship between organizational justice (OJ) and turnover intentions (TI) among hotel managers. The sample comprised 254 lower and middle-level managers from 26 medium-sized hotels (3 and 4- star) in the Klang Valley area. Organizational Justice was measured based on the three-dimensional measures of distributive justice (DJ), procedural justice (PJ), and interactional justice (IJ). Turnover intentions were measured using a five-item. It was hypothesized that distributive justice, procedural justice, and interactional justice perceptions were negatively related to turnover intentions. Results from the regression analyses revealed that only distributive justice and procedural justice have a significant negative effect on managers’ turnover intentions. Interactional justice however, did not support the proposed relationship.